The shadows of total war : Europe, East Asia, and the United States, 1919 - 1939 : [papers presented at a conference held in Aug. 1999 in Münchenwiler, Switzerland as the fourth of a series of five conferences] - Chickering, Roger 1942- Hrsg; Deutsches Historisches Institut Washington DC (Publications of the German Historical Institute, Washington, D.C., 2003)
The politics of war and peace in the 1920s and 1930s / Gerhad L. Weinberg -- War and society in the 1920s and 1930s / Hew Strachan -- Plans, weapons, doctrines: the strategic cultures of interwar Europe / Dennis E. Showalter -- Religious socialism, peace, and pacifism: the case of Paul Tillich / Hartmut Lehmann -- No more peace: the militarization of politics / James M. Diehl -- The war's returns: the care of disabled veterans in Britain and Germany / Deobrah Cohen -- The impact of total war on the practice of British psychiatry / Edgar Jones and Simon Wessely -- Sore loser: Erich Ludendorff's total war / Roger Chickering -- Strangelove, or how Ernst J(c)ơnger learned to love total war / Thomas Rohkr(c)Þmer -- Shadows of total war in French and British military journals, 1918-1939 / Timo Baumann and Daniel Marc Segesser -- Yesterday's battles and future war: the German official military history, 1918-1939 / Markus P(c)œhlmann -- 'The study of the distant past is futile': American reflections on new military frontiers / Bernd Greiner -- 'Not by law but by sentiment': Great Britain and imperial defense, 1918-1939 / Benedikt Stuchtey -- 'Blitzkrieg' or total war? war preparations in Nazi Germany / Wilhelm Deist -- The legion condor: an instrument of total war? / Klaus A. Maier -- Stalinism as total social war / Hans-Heinrich Nolte -- Total colonial warfare: Ethiopia / Giulia Brogini K(c)ơnzi -- Japan's wartime empire in China / Louise Young